Math, asked by venu568, 7 months ago

Factorize (i).x3 - 2x2 - x+2​

Answers

Answered by sheelverma2005
3

Answer:

Here is ur answer.....

Attachments:
Answered by Loveleen68
2

Answer:

Let p(x) = x3–2x2–x+2

Factors of 2 are ±1 and ± 2

Now,

p(x) = x3–2x2–x+2

p(−1) = (−1)3–2(−1)2–(−1)+2

= −1−2+1+2

= 0

Therefore, (x+1) is the factor of p(x)

Now, Dividend = Divisor × Quotient + Remainder

(x+1)(x2–3x+2) = (x+1)(x2–x–2x+2)

= (x+1)(x(x−1)−2(x−1))

= (x+1)(x−1)(x-2)

Attachments:
Similar questions